(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article analyzes the historical development of the Maturidiya kalam school, its main representatives and stages of doctrine formation. The research focuses on the evolution of the Maturidiya school in the 9th-13th centuries, its role and significance in Mawarannahr. The article examines the scientific heritage of Abu Mansur Maturidi and his followers, the relationship of Maturidiya teaching with the Hanafi school, and ideological rivalry with the Ash’ari movement. The spread and stages of development of the school in the Mawarannahr region are also studied based on historical sources. According to research results, the Maturidiya school was formed as an independent theological direction in the 9th-13th centuries and played an important role in the religious and spiritual life of the region.